Safety of Herbal Medicines: Clinical and Pharmacological Aspects - O. A. Demidova; V. V. Arkhipov; M. V. Zhuravleva; T. A. Alexandrova; A. A. Alexandrov (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2020)
Herbal medicines make up a large part of all medicinal products in the Russian market. Complex combinations of biologically active substances that are used as components in herbal medicines not only determine their therapeutic efficacy, but can also cause adverse reactions. The aim of this review was to analyse data on adverse effects of herbal medicines, and reasons and mechanisms behind their development. Special attention should be given to hepatotoxic and nephrotoxic effects of biologically active substances that are used as components in herbal medicines, because liver and kidney failure may lead to life-threatening conditions. The paper addresses hepatic adverse effects, including sinusoidal obstruction syndrome, caused by toxic biologically active substances of the pyrrolizidine alkaloids group. The paper summarises data on herbal medicines and toxic biologically active substances causing acute kidney injury and chronic kidney disease. It analyses potential clinically significant interactions that may occur during co-use of herbal and other types of medicines due to their pharmacokinetic and pharmacodynamic interactions. Further research involving collection, systematisation, and analysis of adverse effects of herbal medicines used alone or in combination with other medicinal products is needed to improve the safety of pharmacotherapy.